The Juggernaut of Modernity Collapses. The Crisis of Social Planification in the Post COVID-19 era - Lusardi, Roberto; Tomelleri, Stefano (Frontiers in Sociology, 2020)
This article arises from the urgent need to reflect on the current situation resulting from the dramatic consequences of a crisis which appears to be epochal and which, as sociologists, questions us at first hand. This is to understand the socio-cultural, economic and technological processes that triggered it and to attempt to imagine future scenarios. At the dawn of the third millennium, it seems as if the juggernaut of modernity, with its dream of unlimited progress and cargo of unconditional trust in instrumental rationality, has abruptly slowed down. The pandemic challenges contemporary society to develop a different weltanschauung, alternative to the performative and conformist idea of social planification supported by the neoliberal paradigm. It compels us to finally acquire the consciousness that the complexity of knowledge and global interdependency require collective awareness, political participation and shared responsibility.